Immunoexpression of P16 and Ki 67 in oral squamous cell carcinoma: Association with clinicopathological parameters. - Shadan Mohamad Omer; Payman Anwar Rashid (Erbil Dental Journal)
Background and Objectives: Oral squamous cell carcinoma (OSCC) is considered as a major health problem worldwide and has been associated with high recurrence rate and poor prognosis. Advances in understanding of OSCC have not improved the outcome in their management significantly. Many studies have focused on the roles of biomolecular markers in OSCC. The use of p16 and Ki67 as biomarkers of biological behavior of oral squamous cell carcinoma is contro-versial. This study aimed to determine immunoexpression of P16 and Ki67 in oral squamous cell carcinoma and to evaluate their association with various clinicopathological parameters. Materials and Methods: Fifty cases of squamous cell carcinoma from different locations in the oral cavity were included in this cross sectional study. The cases were collected from Rizgary Teaching Hospital and Private Laboratories in Erbil city during a period of eight months from October 2018 to May 2019. The expression of p16 and Ki 67 were evaluated immunohistochemically; the findings were correlated with the age of the patients, gender, site of the tumor and grade of the tumor. Result: A total of 50 patients with oral squamous cell carcinoma were enrolled in this study the age ranged from 33 to 89 years, with a mean age ± SD of (64.24 ±12.01) years and more than half (52.0%) of them were males. Lower lip was the most common site of the tumor followed by upper lip and tongue (42.0%, 26.0% and 18.0%, respectively). Histopathological findings of the tumor showed that (54.0%) of the patients had moderately differentiated squamous cell carcinoma. However, (84.0%) of the patients showed negative expression of P 16, while Ki 67 expression was positive among (76.0%) of them. No significant statistical association were found between immunoexpression of p16 and age, sex of patient, site of the tumor and grade of the tumor (P=0.67, P=0,095, P=0.696, P=0.454 respectively). No significant statistical association were found between immunoexpression of Ki67 and age, sex of patient, site of the tumor and grade of the tumor (P=0.637, P=0,411, P=0.353, P=1.00 respectively). Conclusion: in relation to the results obtained in this study no significant association were found between P16 and Ki 67 immunoexpression in oral squamous cell carcinoma with clinicopathological parameters. Further researches have to be designed to better understand the role of p16 and Ki 67 in OSCC.